2020
DOI: 10.1186/s12891-020-3045-7
|View full text |Cite
|
Sign up to set email alerts
|

A registry based analysis of the patient reported outcome after surgery for trapeziometacarpal joint osteoarthritis

Abstract: Background: The aim of the study was to evaluate patient reported outcome measures (PROM) before and after trapeziectomy with or without ligament reconstruction and tendon interposition for trapeziometacarpal joint arthritis with special focus on possible differences due to gender, age and surgical method. Methods: Data from the Swedish quality registry for hand surgery (HAKIR) was analyzed preoperatively, 3 months and 1 year postoperatively for 1850 patients (mean age 63 years, 79% women). Results: One year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
4
13
1
1
Order By: Relevance
“…The approximately one third response rate in HAKIR during the study period may have impacted on the representativeness of the data, thereby affecting interpretation. The response rate was at the same level as previously reported 10,29,30 , with no clear explanation for attrition. Response rates have improved over time since HAKIR started in 2010, but further improvement is needed.…”
Section: Discussionsupporting
confidence: 78%
“…The approximately one third response rate in HAKIR during the study period may have impacted on the representativeness of the data, thereby affecting interpretation. The response rate was at the same level as previously reported 10,29,30 , with no clear explanation for attrition. Response rates have improved over time since HAKIR started in 2010, but further improvement is needed.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, pain is the symptom causing disability for patients with thumb osteoarthritis and is therefore the main indication for surgery. 17 A large ES at 12 months follow-up for all included pain questions (item 1-3) in HQ-8, as well as the question concerning ability to perform daily activities, was therefore as expected. Another example of expected ES is the improvement of numbness/tingling in fingers (item 6) following a carpal tunnel release.…”
Section: Discussionsupporting
confidence: 67%
“…We were able to define a revision algorithm that can be used as a decisionmaking aid when a patient presents with residual symptoms after resection arthroplasty. After primary thumb CMC surgery, reported pain values at rest range from 0.9 to 1.2 and 1.8 to 3.0 (during activities) (Marks et al, 2019;Wilcke et al, 2020), which are lower, and indicative of less pain compared with our respective scores of 1.6 and 2.7 after revision surgery. For hand function, brief MHQ scores of 62 to 83 (indicative of higher hand function) were reported after primary surgery (Efanov et al, 2019;Marks et al, 2019;Waljee et al, 2011) compared with the lower (worse) score of 63 in this revision series.…”
Section: Discussionmentioning
confidence: 48%
“…The results of this study showed that patients were satisfied with the outcome of their thumb CMC revision surgery, yet there were still some residual symptoms after revision. Although the need for revision after resection arthroplasty is rare in cases of thumb CMC OA, the outcome after further surgery is less favourable than that reported after primary thumb CMC replacement arthroplasty (Efanov et al, 2019;Marks et al, 2019;Waljee et al, 2011;Wilcke et al, 2020). Therefore, it is essential to inform the patients about the possibility of persisting symptoms if revision surgery is required.…”
Section: Discussionmentioning
confidence: 99%